Biomechanical energy harvesting for wearable and mobile devices: State-of-the-art and future directions. (1st September 2022) - Liu, Mingyi; Qian, Feng; Mi, Jia; Zuo, Lei
Highlights: The applications of biomechanical energy harvesting are reviewed. The excitation sources and modulations are analyzed and categorized. The methods of energy conversion are summarized and compared. The prospects of biomechanical energy harvesting are presented. Abstract: Wearable and mobile devices, such as smartphones, smartwatches, wearable medical devices, etc ., have become an important part of our daily life. Most of these devices are powered by electrochemical batteries, which have limited energy capacity, need periodic replacement or recharging, and lead to environmental concerns. On the one hand, there is a huge amount of energy stored in the human body and the energy dissipation rate is more than 100 Watts. While on the other hand, the power requirement of typical wearable and mobile devices is less than 1 Watt and keeps decreasing as a result of the rapid development of technologies. Extracting a small amount of energy from the human body can provide enough power for wearable/mobile devices, and enable a convenient, sustainable, eco-friendly, and self-powered alternative to batteries. Many biomechanical energy-harvesting devices have emerged in recent years, of which the excitation source, mechanical modulation, energy conversion method, and performance are vastly different from one another. However, no comprehensive work has been found in the literature that conducted systematical review of the pioneer works from the perspective of modeling of biomechanical energy harvesters. This work reviews the modeling and performance of the state-of-the-art biomechanical energy harvesting devices and classifies them into three categories in terms of excitation mechanisms, specifically, relative-motion-excited, inertia-excited, and force-excited. Different energy-conversion transducers are analyzed and compared, including electromagnetic, piezoelectric, electrostatic, and triboelectric. The evaluation metrics are defined for fair comparisons. The results show that biomechanical energy harvesting has a promising application prospect in many areas, such as health care monitoring systems and wearable electronics, and the current power output and density could be up to 5 W and 10 W/kg. Energy harvesting from negative muscle work may reduce the metabolic cost of human motion while harvesting electrical power. Meanwhile, the review also reveals potential problems that hind the commercialization and practical applications of biomechanical energy harvesting technologies, such as the cost, invasiveness to human body, and interference to human dynamics.